2023
DOI: 10.1177/11795549221140781
|View full text |Cite
|
Sign up to set email alerts
|

TERT Mutations in Non–Small Cell Lung Cancer: Clinicopathologic Features and Prognostic Implications

Liu Yang,
Meng Wang,
Na Li
et al.

Abstract: Introduction: The associations between the clinical characteristics of non–small cell lung cancer (NSCLC) and mutations in telomerase reverse transcriptase ( TERT) gene remain unclear. In this study, we used next-generation sequencing (NGS) to investigate the incidence rate and clinical correlates of TERT mutations in patients with NSCLC. Methods: In total, 283 tumor samples from patients with NSCLC were tested using an NGS panel from September 2017 to May 2020. The genetic testing results and clinical data of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Previous studies have suggested that TERT mutations are associated with a poor prognosis in tumors, such as thyroid malignancies, melanoma and gliomas [39][40][41][42]. Yang et al found TERT mutations were detected in 11% of patients with NSCLC, of which TERT mutation carrier status was an independent risk factor for poor prognosis [43]. Likewise, TERT mutations were found in the CSF of 11.43% of patients in LM with LUAD and these patients had worse prognosis in our study.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have suggested that TERT mutations are associated with a poor prognosis in tumors, such as thyroid malignancies, melanoma and gliomas [39][40][41][42]. Yang et al found TERT mutations were detected in 11% of patients with NSCLC, of which TERT mutation carrier status was an independent risk factor for poor prognosis [43]. Likewise, TERT mutations were found in the CSF of 11.43% of patients in LM with LUAD and these patients had worse prognosis in our study.…”
Section: Discussionsupporting
confidence: 66%
“…Interestingly, patients with ulceration or higher tumor thickness showed significantly higher TERT copy numbers in patients with acral melanoma 16 . Furthermore, TERT copy number alterations in solitary fibrous tumors and TERT mutations in non-small cell lung cancer could be associated with a higher risk of metastasis 18 , 19 . Interestingly, RNA sequencing analysis unveiled a connection between the expression of TERT and genes related to cell migration.…”
Section: Discussionmentioning
confidence: 99%